Why Does Carbon Emission Disclosure Matter? Exploring Its Impact on Firm Value: A Case Study of Sharia-Compliant Companies in Indonesia - Hakim, Lukman; Asyrof, Rifqi Aqil; Sjahbandi, Haykal Abdul Adil; Awinardi, Harish; Rizaldi, Muhammad (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
The large amount of carbon emissions in Indonesia with a percentage reaching 4.1% of total global emissions has made Indonesia ranked 5th as a country that contributes the most CO2 emissions in the world during 1850-2021 and made the public encourage companies to disclose their carbon emissions. Disclosure of carbon emissions can then affect the company's image to investors which leads to its effect on the level of company value. Therefore, this study aims to examine the effect of disclosure of carbon emissions on the value of Islamic companies in Indonesia. This study uses a quantitative approach by processing secondary data which is panel data using panel data regression analysis and cluster analysis. The sample from the cross-section data includes 30 companies registered with ISSI and issues a company sustainability report, while the sample from the time series data is annual and takes the period 2016-2021. This study uses four control variables, namely earnings per share (EPS), leverage, firm size, and investment opportunity set (IOS). The test results show that partially the variable of disclosure of carbon emissions and simultaneously the variables of disclosure of carbon emissions, earnings per share (EPS), leverage, firm size, and investment opportunity set (IOS) have a significant effect on firm value. This research has implications for companies, governments, and investors related to the disclosure of carbon emissions.